Characterization of Developing Cotton Fibers by Confocal Raman Microscopy - Luis Cabrales; Noureddine Abidi; Felicia Manciu (Fibers, 2014)
Cellulose deposition in developing cotton fibers has been studied previously with analytical techniques, such as Fourier transform infrared spectroscopy (FTIR), High-performance liquid chromatography (HPLC) and Thermogravimetric analysis (TGA). Recent technological developments in instrumentation have made Raman microscopy emerge as an extraordinary analytical tool in biological and plant research. The advantage of using confocal Raman microscopy (CRM) resides in the lateral spatial resolution and in the fact that Raman spectroscopy provides not only chemical composition information, but also structural information. Cross-sections of cotton fibers harvested at different developmental stages were studied with CRM. The Raman bands assigned to cellulose were analyzed. The results of this study indicate that CRM can be used as a tool to study cellulose deposition in cotton fibers and could provide useful information on cellulose deposition during cotton fiber development.